Theme Issue Honoring Professor Robert Verpoorte's 75th Birthday: Past, Current and Future of Natural Products Research - Choi, Young Hae; Jang, Young Pyo; Dai, Yuntao; Salomé-Abarca, Luis Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This theme issue is to celebrate Professor Robert Verpoorte's 75th birthday. Prof. Verpoorte has been working in Leiden University over 40 years. There is no need to dwell upon the contributions of Dr. Verpoorte to plant-derived natural products research during his whole life. Dr. Verpoorte was a highly productive scientist throughout his academic career, with over 800 scientific publications in the form of research papers, books, and book chapters. His research interests are very diverse, cover- ing numerous topics related to plant-based natural products such as plant cell biotech- nology, biosynthesis, metabolomics, genetic engineering, and green technology, as well as the isolation of new biologically active compounds. He has left indelible footprints in all these fields, and he is widely recognised as a pioneer in the work of the biosynthesis of indole alkaloids, NMR-based metabolomics, and green technology in natural products production. As close friends and colleagues who have been in nearly daily contact with him over the last 20 years viewing all of these remarkable scientific contributions, we felt compelled to recognize this by the publication of a Special Issue of this journal dedicated to him.Thus, this Special Issue has now finally been released with the help of many of his colleagues and former students as a token of our gratitude to his impressive work.The Special Issue covers five main natural products topics: (1) chemical profiling and metabolomics, (2) separation/isolation and identification of plant specialized metabolites, (3) pharmacognosy of natural products to identify bioactive molecules from natural prod- ucts, (4) novel formulation of natural products, and (5) overview of natural products as a source of bioactive molecules.